Differences in the Structural Chemical Composition of the Primary Xylem of Cactaceae: A Topochemical Perspective - Maceda, Agustín; Soto-Hernández, Marcos; Peña-Valdivia, Cecilia B.; Trejo, Carlos; Terrazas, Teresa (Frontiers in Plant Science, 2019)
The xylem of Cactaceae is a complex system with different types of cells whose main function is to conduct and store water, mostly during the development of primary xylem, which has vessel elements and wide-band tracheids. The anatomy of primary xylem of Cactaceae has been widely studied but little is known about its chemical composition. The aim of this study was to determine the structural chemical composition of the primary xylem of Cactaceae and to compare it with the anatomy in the group. Seeds from eight cacti species were used, representing the Pereskioideae, Opuntioideae, and Cactoideae subfamilies. Seeds were germinated and growth for eight months. Subsequently, only the stem of the seedling was selected, dried, milled and processed following the TAPPI T-222 om-02 norm; lignin was quantified using the Klason method and cellulose with the Kurshner-Höffer method. Using the Fourier Transform Infrared Spectroscopy, the percentage of syringyl and guaiacyl in lignin was calculated. Seedlings of each species were fixed, sectioned, and stained for its anatomical description and fluorescence microscopy analysis for the topochemistry of the primary xylem. The results showed that there were significant differences between species (p<0.05), except in the hemicelluloses. Through a principal component analysis it was found that the amount of extractive-free stem and hot water soluble extractives were the variables that separated the species, followed by cellulose and hemicelluloses, since the seedlings developed mainly parenchyma cells and the conductive tissue showed vessel elements and wide-band tracheids, both with annular and helical thickenings in secondary walls. The type of lignin with the highest percentage was guaiacyl-type, which is accumulated mainly in the vessels, providing rigidity. Whereas in the wide-band tracheids from metaxylem, syringyl lignin accumulated in the secondary walls S2 and S3, which permits an efficient flow of water and gives the plant the ability to endure difficult conditions during seedling development. Only one species can be considered to have paedomorphosis, since the conductive elements had a similar chemistry in primary and secondary xylem.